Stres Kerja Karyawan - Kusumajati, Dian Anggraini (Bina Nusantara University, 2010)
Stress is unavoidable part of an employee in one organization. There are reasons why employees having stress at work. Stress is a contraction when somebody feels one problem has threatened himself. There are kinds of stress kind, like hypo-stress, eu-stress, hyper-stress, and distress. Stress sources in working environment are environment factors, organizational stressor, group stressor, and individual stressor. Besides, there are also factors caused working stresses like biologic, social/cultural, psychodynamic, rational, experiential, and spiritual. After defining sources and factors from working stress, there are ways to overcome them which the organization should do to help the employees; like peer counseling or peer support group, in-house support, employee assistance program, and mediation facility; which will reduce employees’ stressful at work.